HIGH-STAKES TESTING IN NEOLIBERALISM ERA - Maya Puspitasari; Muhammad Arifin Pelawi (Fakultas Keguruan Ilmu Pendidikan Universitas Ibn Khaldun Bogor, 2023)
A high-stakes test has been indicated to be negatively linked to teachers and students in the classroom. However, little is known about the impact of such tests on the teachers and students or those who are involved indirectly in their lives. Using an individual interview with eight English teachers from eight junior secondary schools, this study examines the correlation between the high-stake test with performativity mechanism in the pincer of markets and neoliberalism. Thematic analysis was used to analyse the qualitative data taken from the interviews. The findings indicated how test results were used as a source of promotion by schools to give stakeholders the knowledge they needed to engage in the marketized educational system fully. For school administrators and policymakers, the conclusions of this article had significant ramifications. High-stakes assessments were logically sound and theoretically justifiable, but a reliance on them too much foreshadowed replacing traditional educational ideals with the market value of education. The study offered fundamental new insights into high stakes testing as a tool of social control and oppression for students, teachers, and schools for adopting a neoliberal paradigm in education. In addition to impeding learning and teaching, the employment of high-stakes tests as performativity mechanisms also altered the work of schools and teachers, who were the front liners of the educational system.